Regenerative treatment of canine osteogenic lesions with Platelet-Rich Plasma and hydroxyapatite: a case report - Barbaro, Katia; Marconi, Giorgio; Innocenzi, Elisa; Altigeri, Annalisa; Zepparoni, Alessia; Monteleone, Valentina; Alimonti, Cristian; Marcoccia, Daniele; Ghisellini, Paola; Rando, Cristina; Ottoboni, Stefano; Rau, Julietta V.; et al. (Frontiers in Veterinary Science, 2024)
IntroductionThis study examined the efficacy of a therapy based on a combination of Platelet Rich Plasma and hydroxyapatite nanoparticles in a severe clinical case involving a young Rottweiler with a complex spiral fracture of the tibia.MethodFollowing a worsening of the lesion after traditional surgical intervention, the subject was treated with the combined therapy. X-rays were taken at the following stages: immediately post-surgery, four weeks post-surgery, and 10 days post-treatment. Fracture gap and callus density measurements were obtained using ImageJ analysis, allowing for a detailed quantitative assessment of bone regeneration over time.ResultsPost-operative radiographs indicated a clinical worsening of the fracture, revealing an increased fracture gap due to bone loss. However, significant improvements were observed ten days following the treatment, with a marked reduction in fracture gaps and increased callus density. These results demonstrated a notable acceleration in bone healing and callus formation compared to typical recovery times for similar lesions.ConclusionThe method showed potential for enhancing osteogenic regeneration, facilitating faster healing of serious orthopedic injuries compared to traditional methods.